Pengaruh Budaya Organisasi, Kompetensi dan Reward Terhadap Kinerja Karyawan Pada Kantor Jasa Penilai Publik (KJPP) Di Banjarmasin - Ridha Affandy; Hairudinor (Program Magister Ilmu Administrasi Bisnis FISIP Universitas Lambung Mangkurat, 2024)
Abstract: The research location was at the Public Appraisal Services Office (KJPP) in Banjarmasin, the research sample was 72 respondents, with the characteristics of the respondents being KJPP employees in Banjarmasin. Questionnaires are used for data collection and data processing to test hypotheses. Next, hypothesis testing uses multiple linear regression analysis. The results of the research are that Organizational Culture has an insignificant effect on employee performance, Competency has an insignificant effect on Employee Performance, Rewards have a significant effect on performance, and Organizational Culture, Competency and Rewards simultaneously have a significant effect on Employee Performance Keywords: Organizational Culture, Competency, Rewards, Employee Performance